Nonsyndromic Craniosynostosis - Garza, Rebecca M.; Khosla, Rohit K. (Seminars in Plastic Surgery, 2012)
Nonsyndromic craniosynostosis is more commonly encountered than syndromic cases in pediatric craniofacial surgery. Affected children display characteristic phenotypes according to the suture or sutures involved. Restricted normal growth of the skull can lead to increased intracranial pressure and changes in brain morphology, which in turn may contribute to neurocognitive deficiency. Management has primarily focused on surgical correction of fused sutures prior to 12 months of age to optimize correction of the deformity and to ameliorate the effects of increased intracranial pressure. However, emphasis has recently shifted to better understanding the pathogenesis of neurocognitive impairment observed in these children, along with genetic mutations that contribute to premature suture fusion. Such understanding will provide opportunities for earlier and more specific neurocognitive interventions and for the development of targeted genetic therapy to prevent pathologic suture fusion.The authors review the common types of nonsyndromic craniosynostosis and the epidemiological, genetic, and neurodevelopmental details that are currently known from the literature. In addition, they present the rationale for surgical correction, offer suggestions for timing of intervention, and present some nuances of techniques that they find important in producing consistent results.
Keywords: nonsyndromic craniosynostosis; craniosynostosis; cranial suture; neurocognitive development